The hidden human rights curriculum of surveillance cameras in schools: due process, privacy and trust. Issue 1 (2nd January 2018) - Perry-Hazan, Lotem; Birnhack, Michael
Abstract: This article explores how school principals integrate Closed Circuit TV systems (CCTVs) in educational practices and analyses the pedagogical implications of these practices through the lens of human rights. Drawing on interviews with school principals and municipality officials, we found that schools use CCTVs for three main purposes: (1) Discipline: gathering evidence by semi-legal procedures, which replace educational processes and are inattentive to pupils' voices; (2) Monitoring: real-time surveillance of pupils, which includes both caring and policing practices; and (3) Producing trust, by refraining from accessing the footage. This usage attempts to invert the concern that CCTVs undermine trust, but it may prove a double-edged sword if the pupils do not believe the principal. We argue that each of these approaches shapes the schools' hidden human rights curriculum, by which pupils learn about due process, privacy, and autonomy, and about the power relations that determine the scope of these rights.